Secularism in the Application of Islamic Family Law in the Philippines - Ali, Anshari Pangaga (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Secularism in the Application of Islamic Family Law in the Philippines